Better Understanding the Timing Of Androgen Deprivation Trial Outcomes: Impacts of Prior Androgen Deprivation Therapy. Issue 3 (28th March 2022) - Stensland, Kristian D; Devasia, Theresa; Caram, Megan E V; Chapman, Christina; Zaslavsky, Alexander; Morgan, Todd M; Hollenbeck, Brent K; Sparks, Jordan B; Burns, Jennifer; Vedapudi, Varsha; Duchesne, Gillian M; Tsodikov, Alexander; et al.
Abstract: Background: The Timing Of Androgen Deprivation (TOAD) trial found an overall survival benefit for immediate vs delayed androgen deprivation therapy (ADT) for prostate-specific antigen (PSA)–relapsed or noncurable prostate cancer. However, broad eligibility criteria allowed entry of a heterogeneous participant group, including those with prior ADT exposure, raising concerns about subsequent androgen sensitivity. For these reasons, we completed previously specified subgroup analyses to assess if prior ADT was associated with ADT timing efficacy after PSA relapse. Methods: We examined TOAD trial patient-level data for participants with PSA relapse after local therapy. We performed Kaplan-Meier analyses for overall survival stratified by prior ADT and randomized treatment arm (immediate or delayed ADT). We compared group characteristics using Mann-Whitney U and Fisher exact tests. All hypothesis tests were 2-sided. Results: We identified 261 patients with PSA relapse, 125 of whom received prior ADT. Patients with prior ADT had higher PSA at presentation (12.1 vs 9.0 ng/mL; P  < .001), more cT3 disease (38.4% vs 25.0%; P  = .007), and more likely received radiotherapy as local treatment (80.0% vs 47.8%; P  < .001) but were otherwise similar to patients without prior ADT exposure. Within this prior ADT group, those who received immediate ADT (n = 56) had improved overall survival compared with those who received delayed ADT (n = 69; P  = .02). This benefit was not observed in the group with no prior ADT ( P  = .98). Conclusions: The survival benefit demonstrated in the TOAD trial may be driven by patients who received ADT prior to trial entry. We provide possible explanations for this finding with implications for treatment of PSA-relapsed prostate cancer and future study planning.